KOHESI DAN KOHERENSI LAGU BELLE DALAM OPERA NOTRE-DAME DE PARIS: SUATU KAJIAN WACANA (DISCOURSE ANALYSIS OF BELLE THE NOTRE-DAME DE PARIS) - Maydita Piety Prastitasari; Pratomo Widodo; Pangesti Wiedarti (Metalingua: Jurnal Penelitian Bahasa, 2021)
The aims of this study are to describe the cohesion markers, coherence markers, and its situation and cultural context contained in the lyrics of “Belle'' the “Notre-Dame de Paris”. This study used the scrutinize method for collecting data by applying reading technique, SBLC (non-participant observation) technique, and note-taking technique. The data was analysed by using division classifying technique, replacing technique, expanding technique, and marker identification technique. The results of this study showed that: (1) the cohesion markers found based on the analysis included grammatical and lexical cohesion. Those markers are references (63 data), conjunctions (4 data), synonymy (6 data), repetitions (4 data), collocations (2 data), and equivalence (1 data); (2) The coherence markers found on this analysis are relationship of addition meanings (1 data), relationship of time meanings (3 data), relationship of comparison meanings (2 data), relationship of effect meanings (1 data), relationship of explication meanings (4 data), and relationship of usability meanings (5 data); (3) Based by situation and cultural context analysis, this data contains the love story among Quasimodo, Frollo, and Phœbus towards Esmeralda, the gypsy dancer.